Knowledge and Preference for Refractive Surgery and Preferred Methods of Refractive Correction among Patients with Significant Refractive Errors Attending Bharatpur Eye Hospital, Nepal - Giri, Puspa; Bhandari, Gopal; Sah, Ranjeet (Journal of Nobel Medical College, 2020)
Background: Refractive errors are a major cause of defective vision in all age groups. Although contact lens and refractive surgery are popular, still spectacles are the traditional and most widely used method of optical correction. The main objective of the study was to determine the knowledge and preference for refractive surgery and preference for refractive correction. Materials and Methods: Questionnaire based study was conducted among 252 participants aged between 22-40 years with significant refractive errors (>±1.00D) for a period of three months between June to August 2017. Participants who had prior refractive surgery and not willing to participate were excluded from the study. Results: One hundred and forty (55.6%) were males and majority (76.6%) of the participants were in the age range 22-30 years. Myopia (60%) was more prevalent followed by astigmatism (38%) and hypermetropia (2%) with refractive power between 1-3 D in 72.5% of participants. Only 61(24%) of the participants had knowledge about refractive surgery. Forty three percentages of them knew from their friends, internet was source of information for 36% and only 19% of them knew from eye care professionals. Majority (87.3%) preferred spectacles 4.8% preferred contact lens and only 8% preferred refractive surgery as methods of refractive correction. Only 44% showed willingness for refractive surgery when available at Bharatpur Eye Hospital. Participants with prior knowledge (p=0.002), higher refractive error and longer duration of glass wear (P=0.005) had more preference for refractive surgery. Conclusion: The knowledge, preference and willingness for refractive surgery were less with spectacle being the most preferred methods of refractive correction.